Development of Online STEM Learning Program for the Preparation of Prospective 21st Century Biology Teacher - Setiono Setiono; Sistiana Windyariani (BIOEDUKASI, 2023)
The development of online STEM (science, technology engineering and mathematics) learning programs for prospective Biology teacher students is essential because STEM education can provide several necessary skills needed by biology teachers in the future. This research aims to produce an online STEM learning program by utilizing existing resources around the school. The research method used in this study is a mixed method with a research design: Embedded Experimental Model. Several biology education students (n= 15) were involved in this research. The research began with a preliminary study, drafted a STEM learning program, and developed and implemented a STEM learning program. The instruments used in this study were: learning program assessment sheets, textbook assessment sheets, STEM concept understanding tests, student participation assessments, product assessments, communication skills assessments, EDP assessment rubrics, teaching device assessment rubrics, project assessment rubrics, manufacturing assessment rubric learning videos, online learning observation sheets, and learning observation sheets. Prior to use, all instruments were validated by colleagues and experts. The results of the validation show that, in general, the online STEM learning program and its accessories are suitable for program testing. In terms of the programs being developed, they are effective in improving the abilities of 21st-century biology teacher candidates, and this can be seen from the N-gain score; of 06 obtained. The results of this effectiveness test indicate that the developed learning program can improve the 21st-century abilities of prospective biology teacher student.